(untitled) (Trinity Journal of Management, IT & Media (TJMITM), 2018)
The aim of the study is to examine investors’ perception towards mutual funds in India and also to identify attributes that are crucial for taking investment decisions in mutual funds. Stratified random sampling has been used for collection of responses through structured questionnaire. Factor analysis was used for data analysis using SPSS to find out factors that have impact on investors’ perception. During the factor analysis, all the eighteen items were reduced to eight factors explaining 65.18% of variance. The factors were selected on the basis of eigenvalues and only eight factors having eigenvalue greater than one were retained to interpret the results. Eight factors were found having maximum (13.56%) for first factor (funds information related attributes) and lowest (5.85%) for the eighth factor (funds capital appreciations attribute). The model was tested using reproduced correlations matrix and found fit.